Reading South Bangka from Within: An Ethnographic Exploration of Cultural Practices and Social Structures - Muhammad Safwan Jamil; Tuzhara Ramadhanty Majid; Wisnu Setiadi (Prodi Sosiologi FISIP Universitas Teuku Umar, 2026)
This study aims to understand how the cultural practices and social structures of the South Bangka community are formed, sustained, transformed, and maintained in the contemporary social context. Using an ethnographic approach, this study examines cultural dynamics such as traditional customs, religious rituals, household economics, gender relations, kinship systems, and social changes resulting from modernization, migration, and industrial expansion. This study also examines local social structures, including kinship relations, informal hierarchies, patronage, economic structures, and power relations that bind individuals and groups in everyday social life. The results show that the cultural practices of the South Bangka community are flexible but still maintain core values such as mutual cooperation, solidarity, social harmony, and respect for ancestors. Modernization does not necessarily eliminate tradition but encourages the community to adapt cultural practices to the needs of the times. In addition, social structures have been shown to play an important role in shaping patterns of interaction, role distribution, and conflict resolution mechanisms. Interpersonal and group relationships are built through kinship networks, village communities, religious associations, and work relationships, all of which influence social stability and the formation of collective identity. This study concludes that cultural practices and social structures in South Bangka are closely interrelated.